2016
DOI: 10.1515/jvetres-2016-0009
|View full text |Cite
|
Sign up to set email alerts
|

In vitro drug sensitivity in canine lymphoma

Abstract: Introduction: Due to the high heterogeneity of canine lymphoma, the aim of the present study was to test in vitro the chemosensitivity of canine high-grade primary lymphoma cells to various cytostatic drugs commonly used to treat dogs: 4-HO-cyclophosphamide, doxorubicin, dexamethasone, prednisolone, vincristine, etoposide, chlorambucil, lomustine, and cytosine arabinoside. Material and Methods: To determine the cell viability and drug ability to induce apoptosis two different tests were used: an MTT assay and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…There are few studies which have investigated pharmacodynamic end points of CA in dogs, both of which evaluated canine lymphoma and leukaemia cell lines (Pawlak et al., 2014; 2016). While Pawlak et al., (2016) found that CA demonstrated moderate to high efficacy as determined by the percentage of apoptotic/dead neoplastic cells following incubation with CA at a concentration of 1 µg/ml, neoplastic cells can exhibit altered chemosensitivity and pharmacodynamic properties when compared to other cell populations. Thus, these results may not accurately predict CA activity against the non‐neoplastic inflammatory cells that mediate MUE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few studies which have investigated pharmacodynamic end points of CA in dogs, both of which evaluated canine lymphoma and leukaemia cell lines (Pawlak et al., 2014; 2016). While Pawlak et al., (2016) found that CA demonstrated moderate to high efficacy as determined by the percentage of apoptotic/dead neoplastic cells following incubation with CA at a concentration of 1 µg/ml, neoplastic cells can exhibit altered chemosensitivity and pharmacodynamic properties when compared to other cell populations. Thus, these results may not accurately predict CA activity against the non‐neoplastic inflammatory cells that mediate MUE.…”
Section: Discussionmentioning
confidence: 99%
“…It is S‐phase specific and causes competitive inhibition of DNA polymerase in mitotically active cells, thus preventing DNA replication, halting the cell cycle and precipitating apoptosis (Gmeiner et al., 2003; Scott‐Moncrief et al., 1991; Withrow et al., 2012). It has therefore been used for the treatment of multiple disease processes involving pathologic cell replication, including lymphoma (involving the bone marrow or central nervous system and in cases of relapse), leukaemia and optic neuritis of non‐infectious origin (Gillem et al., 2015; Marconato et al., 2008; LaRue et al., 2018; Pawlak et al., 2014, 2016; Bedos et al., 2020; Alvarez et al., 2006). As MUE is highly suspected to be due to a robust T‐cell autoimmune response, CA has been utilized as a treatment option for meningoencephalomyelitis of unknown aetiology (MUE) with the goal of inhibiting the pathologic lymphocyte proliferation associated with this autoimmune disease (Vitale et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the identification of relevant features is a challenge in any biological model. Direct measurements of treatment response in primary tumour samples are almost certainly relevant to treatment response in patients 18 . However, ex vivo assessments of chemosensitivity may not fully capture the behaviour of drugs or cells in vivo, which may render these measures insufficient to fully predict individual treatment responses alone.…”
Section: Discussionmentioning
confidence: 99%
“…Cell‐based ex vivo drug sensitivity assays have been widely studied as a precision medicine tool to recapitulate the tumour microenvironment in vitro and predict in vivo responses in human lymphoproliferative disorders 13‐17 . For canine lymphoma, Pawlak et al reported an in vitro chemosensitivity assay that measures the cytotoxicity of various anticancer reagents in high‐grade primary lymphoma cells 18 . This previous work showed that drug sensitivity varies among individual patients and that a direct measurement of drug response in primary cancer cells is a potential predictor of actual response in the body.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation